Bernard Organ Failure Score in estimation of most severe forms of acute pancreatitis - Glišić Tijana; Šijački Ana; Vuković Goran; Vukojević Vladimir; Subotić Aleksandar (Srpski Arhiv za Celokupno Lekarstvo, 2009)
Introduction. Despite intensive research, efforts and clinical investigations on pathogenesis of acute pancreatitis (AP) and system morbidity during the illness onset, mortality is still very high in the group of severe forms. A significantly high number of patients show moderate, self-limited forms of illness, with a minimal degree of systemic or local complications, with full recovery. However, some of them have a severe form, followed by a high percent of morbidity and mortality, and system organ failure. The distinction between mild and severe forms of AP within 24-48 hours of hospital admission is very important for the treatment of these patients. The usage of multifactorial scoring systems holds a lot of promise, reaching reliability in the disease severity estimation of approximately 70-80%. Objective. The main purpose of this prospective study was to assess the correlation of the Acute Physiology and Chronic Health Evaluation II (APACHE II) and the Bernard Organ Failure Score (BOFS) scoring systems in estimation of disease severity and outcome prediction. Methods. Sixty patients with AP participated in the study, all of them scored with the APACHE II and BOFS scores. The results were used for integration of laboratory and clinical parameters. Results. In our study, we had a highly significant correlation between the APACHE II and BOFS scores from the disease onset until the end of treatment. There was a highly significant correlation between these two scores and the serum C-reactive protein concentration level. Conclusion. The concept of the BOFS score has more advantages than the APACHE II score in the patients with severe forms of AP with organ dysfunction.